House of blight : a novel - Martineau, Maxym M. (Threadmender chronicles, 2025)
"The first novel in a transportive, darkly creative and romantic new gothic fantasy duology from Maxym M. Martineau, for readers of Sarah J. Maas and Rachel Gillig"--